The Role of Youth in The Creation of An Enlightened Society of The New Uzbekistan - Ibragimova Mohinur Sanat qizi (Zien Journals, 2022)
The article reveals the role of youth in the creation of an enlightened society of the New Uzbekistan, the achievements of young people, as well as measures to educate the future of the New Uzbekistan
Keywords: renaissance; education; patriotism; culture